La noción de justicia en la crítica benjaminiana del conocimiento - Catanzaro, Gisela Mara (2011)
The reference to “justice”, persistent in Walter Benjamin’s thought, appears to play a double role in his writings. On one hand, it seems to have a gnoseological value –as in the "Epistemo-Critical Prologue" to The Origin of German Tragic Drama- in so far it allows the critique of the predominant notion of knowledge as discovery. On the other hand, it seems to have a more political meaning, associated to the interruption of social violence, as in “Critique of violence” where “justice” is opposed to the violence of Myth, perpetuated by Law. Nevertheless, being no other than that same social violence what –in Benjamin’s view- expresses and reproduces itself in the methods of discovery, appropriation and codification developed by Science, those two “values” of justice can barely be differentiated or defined on their own in his writings. Bearing this in mind, in the first and second sections of this article we focus on the idea of justice and interpret its protagonism in Benjamin’s thought as a shift with respect to the categories privileged by political Theory and Philosophy –in particular: the notion of freedom -, and in association with terms which had been almost excluded from the vocabularies of modern political thought, such as the idea of happiness. Finally, we explore some of the alternative images of knowledge that, through a reference to justice, Benjamin provides in his last writings.